174k views
2 votes
Use the zero product property to find the solutions to the equation 2x^2+x-1=2

User Quen
by
4.8k points

2 Answers

3 votes

Answer:

x = -
(3)/(2) or x = 1

Explanation:

trust.

User Sqrs
by
5.1k points
4 votes

Answer:

x = 1, x = -
(3)/(2)

Explanation:

Given

2x² + x - 1 = 2 ( subtract 2 from both sides )

2x² + x - 3 = 0 ← in standard form

Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term

product = 2 × - 3 = - 6 and sum = + 1

The factors are - 2 and + 3

Use these factors to split the x- term

2x² - 2x + 3x - 3 = 0 ( factor the first/second and third/fourth terms )

2x(x - 1) + 3(x - 1) = 0 ← factor out (x - 1) from each term

(x - 1)(2x + 3) = 0

Equate each factor to zero and solve for x ← zero product property

x - 1 = 0 ⇒ x = 1

2x + 3 = 0 ⇒ 2x = - 3 ⇒ x = -
(3)/(2)

User YYY
by
4.9k points